Photographing Madrid during the Spanish Civil War. Santos Yubero’s Photographs from the Archivo Regional de la Comunidad de Madrid - de las Heras, Beatriz; Mora, Víctor (Revista General de Información y Documentación, 2014)
The half a million photographs taken between the 20’s and the 70’s by Santos Yubero and kept in the “Archivo Regional de la Comunidad de Madrid” allow us to approach the visual memory of the city of Madrid during the 20th century. This paper presents a study of the photographs that profile Madrid during the Spanish Civil War (1936-1939) in the three different spaces opened in the capital after the uprising of July: the front, the rear and the military rear. After presenting the results of the catalogued photographs (taking into account the captured matter), the effect of the work of Santos Yubero during the Spanish Civil War will be analyzed. To do so, we will study the photographs published in the six different newspapers where Santos Yubero worked during the conflict: ABC (Madrid edition), Ahora, Crónica, La Libertad, La Voz and Mundo Gráfico. This work was made both alone and signing with the photographic agency that Santos Yubero created with Benítez-Casaux brothers. Finally, we will reflect on some characteristics that the photographs of Yubero have as documents to approach the Spanish Civil War.